Households as foci for dengue transmission in highly urban Vietnam. - Katherine L Anders; Le Hong Nga; Nguyen Thi Van Thuy; Tran Van Ngoc; Cao Thi Tam; Luong Thi Hue Tai; Nguyen Thanh Truong; Huynh Thi Le Duyen; Vu Tuan Trung; Duong Thi Hue Kien; Marcel Wolbers; Bridget Wills; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Dengue control programs commonly employ reactive insecticide spraying around houses of reported cases, with the assumption that most dengue virus (DENV) transmission occurs in the home. Focal household transmission has been demonstrated in rural settings, but it is unclear whether this holds true in dense and mobile urban populations. We conducted a prospective study of dengue clustering around households in highly urban Ho Chi Minh City, Vietnam. METHODS:We enrolled 71 index cases with suspected dengue (subsequently classified as 52 dengue cases and 19 non-dengue controls); each initiated the enrollment of a cluster of 25-35 household members and neighbors who were followed up over 14 days. Incident DENV infections in cluster participants were identified by RT-PCR, NS1-ELISA, and/or DENV-IgM/-IgG seroconversion, and recent infections by DENV-IgM positivity at baseline. PRINCIPAL FINDINGS/CONCLUSIONS:There was no excess risk of DENV infection within dengue case clusters during the two-week follow-up, compared to control clusters, but the prevalence of recent DENV infection at baseline was two-fold higher in case clusters than controls (OR 2.3, 95%CI 1.0-5.1, p = 0.05). Prevalence of DENV infection in Aedes aegypti was similar in case and control houses, and low overall (1%). Our findings are broadly consistent with household clustering of dengue risk, but indicate that any clustering is at a short temporal scale rather than sustained chains of localized transmission. This suggests that reactive perifocal insecticide spraying may have a limited impact in this setting.